EVALUASI KINERJA INPUT-OUTPUT PADA SEKTOR AGRIBISNIS SYARIAH: STUDI EMPIRIS EMITEN PERKEBUNAN PERIODE 2021-2024 - Tafarini, Meitry Firdha; Bertliussaza; Purba, Khairul Fahmi; Wardani, Azqia; Yuliani, Maulidia Tri (Journal of Sharia Economics, 2026)
This study aims to evaluate the technical efficiency level of financial performance in agribusiness and sharia plantation sub-sector companies in Indonesia and analyze the impact of sharia compliance on the operational competitiveness of companies. The non-parametric quantitative method of Data Envelopment Analysis (DEA) with the assumption of output-oriented Variable Return to Scale (VRS) was applied to analyze panel data from five major emitters (AALI, LSIP, SSMS, DSNG, and SIMP) that were consistently listed on the Indonesian Sharia Stock Index (ISSI) during the observation period of 2021–2024. The results showed that the average efficiency of the sharia agribusiness industry reached 95.3%, with LSIP and SSMS consistently operating on the efficient frontier curve. The majority of inefficiencies detected in large-scale emitters were caused by Decreasing Returns to Scale (DRS) due to excessive asset accumulation, as well as waste (tabdzir/slacks) in the cost allocation of revenue and operating expenses. The conclusion of this study confirmed that compliance with sharia debt ratio restrictions did not inhibit competitiveness in the global market, but rather functioned as prudent governance that protected companies from the risk of over-leverage and stimulated the achievement of pure technical efficiency. The strategic implications of these findings recommend that agribusiness companies shift to precision agriculture technology intensification and lean supply chain implementation in order to reduce input slack on a sustainable basis.